Together with Well Done Crochect, Knitting the Hope of Free Orphaned Middle School Teachers - Hapsari, Andriyani; Andriani, Jeni; Astuti, Fifit (Unram Journal of Community Service, 2024)
This community service activity was carried out by a team of lecturers and students from the Faculty of Economics and Business and the Faculty of Engineering, Pamulang University with Well Done Crochet partners with grant funding from the Ministry of Education and Culture of The Republic of Indonesia . The aim of this activity is in line with the first sustainable development goal, namely ending poverty in all forms throughout the world. The focus of this goal is on efforts to eradicate extreme poverty and empower those living in vulnerable conditions. The establishment of Well Done Crochet was initially to provide additional income for free school teachers for orphans. The methods or stages used are Identification of Partner Needs, Design and Procurement of Equipment. Operational Testing of Equipment, Operational Assistance, Technology Dissemination to the community/partners, Training, Mentoring, and Monitoring and Evaluation. After going through several stages of these activities, improvements were achieved, including: (a) increasing the skills of knitting teachers regarding various knitting techniques using sentro knitting machines, knitting net bags and needle punch techniques, (b) increasing teachers' knowledge about Business. Canvas and Design thinking models, (c) increasing the knowledge of Well Done Chrochet students about entrepreneurship. This service activity can be said to have succeeded in increasing the creativity of teachers and students to maximize entrepreneurial activities in the craft sector as additional income